Integration of C2C E-Commerce Media in MSMEs to Support the UMKM Go Digital 2030 Program - Nora Listiana (International Publisher, 2024)
The growth of the MSME sector in Indonesia has faced various challenges, especially during the COVID-19 pandemic. A survey of 250 MSMEs revealed that 67% experienced a decrease in revenue. One of the primary issues currently confronting MSMEs is marketing. Poor marketing infrastructure has led to a low level of market orientation among these businesses. As a result, it is crucial for MSMEs to strengthen their competitiveness in an increasingly open and competitive market environment. This study explores the integration of Consumer-to-Consumer (C2C) e-commerce platforms in Micro, Small, and Medium Enterprises (MSMEs) in Depok City, Indonesia, in the context of the UMKM Go Digital 2030 Program. Through a descriptive survey research design using quantitative methods, the study identifies how digital infrastructure and platform usability influence MSME performance. Data from 105 MSMEs were collected using structured questionnaires and analyzed using SPSS. The findings highlight the benefits and challenges of digital integration, offering recommendations to strengthen MSME participation in the digital economy.